Ghrelin and oxidative stress in gastrointestinal tract - Suzuki, Hidekazu (the Society for Free Radical Research Japan, 2011)
Oxidative stress is a major cause of the gastrointestinal damage under physical or psychological stress. Ghrelin exhibits gastroprotective effects and they are supposed to be derived from antioxidant effects. In gastroduodenal mucosal injury, the plasma ghrelin levels increase in response to the demand for gastroduodenal cytoprotection. However, in the condition of Helicobacter pylori-induced gastric mucosal severe atrophy, the plasma ghrelin concentration shifted to lower levels. In diabetic gastroparesis, the regulation of ghrelin secretion is impaired with vagal nerve dysfunction. Selective ghrelin agonist is expected to represent a new class of prokinetic agent. In addition, the plasma ghrelin levels are also enhanced by systemic oxidative stress, and ghrelin exhibits antioxidant effects in many organs, such as heart, pancreas, and lung. This suggests that ghrelin would be an important player as a sensor of systemic oxidative stress.